2019
DOI: 10.1039/c9cp02398d
|View full text |Cite
|
Sign up to set email alerts
|

Humidity transforms immobile surface charges into mobile charges during triboelectric charging

Abstract: Ionic material fragments created by contact stress will react with water to create ions that can transfer between surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…For example, it was reported that the water film could transform immobile surface charges into mobile charges, which can act as charge carriers. 25 Second, the adsorbed water film on the dielectric surface could shield the surface potential during the KFM measurement, leading to the measured surface potential signal being lower than the true surface potential. 40 We argue that the role of the water film on the charge transfer in a metal−dielectric case could not be explained merely by those mechanisms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it was reported that the water film could transform immobile surface charges into mobile charges, which can act as charge carriers. 25 Second, the adsorbed water film on the dielectric surface could shield the surface potential during the KFM measurement, leading to the measured surface potential signal being lower than the true surface potential. 40 We argue that the role of the water film on the charge transfer in a metal−dielectric case could not be explained merely by those mechanisms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, it was found that water molecules could transform immobile surface charges into mobile charges during triboelectric charging. 25 For example, [H(H2O) n ] + and [OH(H2O) n ] − ions and other less common species can enable the conduction. 32 Thus, the water layer can alter the surface conductivity by introducing an additional conducting path through the water film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…106,107 It was also suggested that water ions induced from mechanoions could be the charge carriers due to their energetic preferences. 108 Many studies have claimed that mechanoions and mechanoradicals make major contributions to the triboelectrification. 109 In simultaneous KPFM and MFM measurements on a contact-electrified surface, the generation sites of mechanoradicals and mechanoions were identical (Figure 9c).…”
Section: Mechanism Of Triboelectricitymentioning
confidence: 99%
“…The occurrence of a magnetic signal from a mechanoradical on a rubbed or fractured polymer sample has been the subject of some research, leading to the identification of the molecular structure by resolving the corresponding EPR spectrum . Moreover, because both mechanoions and mechanoradicals are energetically active species, various chemical reactions can be driven, such as surface copolymerization and hydrogen peroxide generation from water. , It was also suggested that water ions induced from mechanoions could be the charge carriers due to their energetic preferences …”
Section: Mechanism Of Triboelectricitymentioning
confidence: 99%